The undergraduate students’ beliefs about English language learning; a survey study in Madurese context - Fithriyah Rahmawati (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2020)
The discussion in line with students’ beliefs about language learning is still popular nowadays since it is believed that the student’s beliefs may influence the language learning process, such as motivation, learning style, and strategies, etc. which later ultimately affected the success of language learning. This study was conducted to investigate how students of the English program at IAIN Madura (State Islamic Institute of Madura), Indonesia, express their beliefs about English language learning. This study was implemented in terms of survey study in which the data was primarily gathered by administering the questionnaire entitled Beliefs About Language learning Inventory (BALLI) of Horwitz’s (1987). The questionnaires were administered to students of English teaching and learning program through Google form. About 144 undergraduate students in the first year have participated in this study.  The finding revealed the students’ beliefs in terms of percentage of agreements in all area of BALLI, namely language aptitude, the strategy of learning and communication, the nature of learning language, motivation and expectation in learning, and the difficulty faced by students